The Institution of Marriage after Same sex Marriage - Gimeno, Beatriz (2009)
This article posits the idea that the recognition of Same-sex marriage, which have been achieved by the Spanish (LGTB) movement, is a non-reformist reform. That is to say rather than a conservative assertion, which modifies the naturalized character of marriage by imposing it on new subjects (homosexuals), it is a deinstitutionalization mechanism. This means that while affirming the full citizenship of the LGTB groups, in other words their social recognition, it also deconstructs marriage in two ways. Firstly, through the understanding of this institution as culturally and socially constructed and therefore subject to subsequent modifications throughout its history. Secondly, Same-sex marriage being a contradiction in itself (from the point of view of an integrated network of meanings and practices) reveals the ‘overflow’ of that same institution.